MENTAL HEALTH DISORDERS AND PRODUCTIVITY: WHICH ARE THE RISK AND MITIGATING FACTORS OF ABSENTEEISM AND PRESENTEEISM? EVIDENCE FROM THE U.S. TECH SECTOR - Víctor Monroy; Esteban Michel (Investigación & Desarrollo)
This paper examines the impact of mental health disorders on Absenteeism and Presenteeism in the workplace. Using data from Open Sourcing Mental Illness (OSMI) surveys conducted between 2017 and 2022 and addressing missing data through multiple imputation via chained equations (MICE), the study employs an ordered logit model to identify the key drivers and deterrents of Absenteeism and Presenteeism. The findings reveal that a history of mental health issues significantly increases both Absenteeism and Presenteeism, while a family history of mental disorders is significantly associated with both Absenteeism and Presenteeism. Additionally, personal stigma surrounding mental illness is identified as a contributing factor to Absenteeism. Interestingly, openness with family and firm size were found to unexpectedly increase Presenteeism. Lastly, the study shows that undergoing therapy is associated with a reduction in Presenteeism by at least 36 percentage points.